2022
DOI: 10.1152/japplphysiol.00082.2022
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based quantification of posterior ocular globe flattening during 60 days of strict 6° head-down tilt bed rest with and without daily centrifugation

Abstract: Spaceflight Associated Neuro-ocular Syndrome (SANS) is associated with acquired optic disc edema, hyperopia, and posterior globe flattening in some astronauts during long-duration spaceflight possibly due to the headward fluid redistribution in microgravity. The goal of this study was to assess whether strict head-down tilt (HDT) bed rest as a spaceflight analog would produce globe flattening and whether centrifugation could prevent these changes. Twenty-four healthy subjects separated into 3 groups underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…12 Increased posterior globe flattening has been a SANS finding that has been replicated in head-down tilt bed-rest studies. 13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Increased posterior globe flattening has been a SANS finding that has been replicated in head-down tilt bed-rest studies. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…12 Increased posterior globe flattening has been a SANS finding that has been replicated in head-down tilt bedrest studies. 13,14 In recent research, Ferguson, et al compared results in patients with increased ICP from IIH with observations in astronauts following long-duration spaceflight to determine the frequency and location of choroidal and retinal folds. The scientists concluded that there are parallels between the choroidal and retinal fold patterns in SANS and IIH, indicating that elevated ICP might play a role in the onset of SANS.…”
Section: Introductionmentioning
confidence: 99%
“…While short-term/intermittent short-radius centrifugation (artificial gravity induction) of participants exposed to HDT reduces muscular deconditioning and orthostatic intolerance, it does not appear to change SANS-like findings. 5,6 We still do not know if ICP is elevated in microgravity, although there are pending efforts that may answer this question. The work presented here 1 gives further evidence that neither ICP nor venous outflow changes are sufficient to explain key findings in SANS such as choroidal folds beyond the optic disc area, and further studies are needed to identify the forces acting on the globe and orbit in microgravity.…”
mentioning
confidence: 99%
“…However, these folds were peripapillary and resembled those seen in individuals with terrestrial IIH and not LDSF. A recently published study using magnetic resonance imaging to assess globe deformation in participants exposed to HDT showed that posterior globe flattening was a frequent occurrence and could persist or even progress in the days following cessation of HDT . Again, this globe flattening was identified in the peripapillary region and did not extend to the macula, making it difficult to implicate presumed peripapillary forces in the development of the choroidal folds noted by Ferguson and colleagues .…”
mentioning
confidence: 99%
See 1 more Smart Citation